Delivery of Anoxic Gas Mixtures in Anaesthesia: Case Report and Review of the Struggle towards Safer Standards of Care. Issue 1 (July 2017) - Pauling, M.; Ball, C. M.
In 1983 a patient at The Alfred Hospital, Melbourne died during general anaesthesia for emergency surgery, in the weeks following maintenance to the operating theatre gas supply. In the ensuing investigation, it was revealed that he had been given 100% nitrous oxide throughout the anaesthetic due to the inadvertent crossing of the nitrous oxide and oxygen pipelines during the repair work. In this article we review the published literature on the delivery of hypoxic and anoxic gas mixtures, and the associated morbidity and mortality. We explore the developments that took place in the delivery of anaesthetic gases, and the unforeseen dangers associated with these advances. We consider the risks to patient safety when technological advances outpaced the implementation of essential safety standards. We investigate the events that pushed the development of safer standards of anaesthetic practice and patient monitoring, which have contributed to modern day theatre practice. Finally, we consider the risks that still exist in the hospital environment, and the need for on-going vigilance.